Kiribati : 2016 Article IV Consultation-Press Release;Staff Report; and Statement by the Executive Director for Kiribati. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Kiribati's recent economic performance has been strong. Growth is estimated to have reached 3.5 percent in 2015, supported by record-high fishing revenue, donor-financed infrastructure projects, and reconstruction in the aftermath of cyclone Pam. The fiscal position has improved markedly in recent years. High fishing revenue contributed to a recurrent fiscal balance of almost 50 percent of GDP in 2015, more than offsetting the increase in recurrent government spending of 13 percent. Growth is projected to moderate somewhat to about 3 percent in 2016, while inflation remains subdued owing to low food and commodity prices.